PENINGKATAN SEKTOR PANGAN PENGELOLAAN HASIL LAUT PADA UMKM BERKAH UTAMA SNACK DENGAN PENERAPAN TEKNOLOGI TEPAT GUNA DIKELURAHAN SINAR JAYA SUNGAILIAT BANGKA - Oktriadi, Yudi; Yuliyanto, Yuliyanto; Josi, Ahmad; Hasdiansah, Hasdiansah; Afriadi, Achmad; Dafri, Nastiar; Gunadi, Ahmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This Community Service Program aims to address production challenges faced by the Berkah Utama Snack business group, which operates in the fishery processing industry, specifically the production of fish crackers and kemplang (fish crackers). The business group, led by Mrs. Rika Trisdasawati, is located in the Sinar Jaya neighborhood of Sinar Jaya Jelutung Village, Sungailiat District, Bangka. The main challenges faced by partners were limited and worn-out production equipment, including worn and unhygienic fish grinding machines, manual kneading processes, and low-capacity packaging equipment. This resulted in a production capacity of only 10 kg per day, insufficient to meet consumer demand. The implementation method for this activity involved six main stages: (1) identifying partner needs through field observations, (2) designing machines according to technical specifications using CAD software, (3) manufacturing machines at the Polman Negeri Babel Mechanical Workshop with the involvement of technicians and students, (4) operational testing with partners, (5) operational mentoring, and (6) technology dissemination to partners. The results of this activity demonstrated significant achievements in the form of the construction and delivery of three production machines. First, a fish grinding machine with a 40x40 mm L-shaped angle iron frame, a 5.5 HP internal combustion engine, and a pulley-belt transmission system. Second, a stainless steel dough mixer with a 550x450x550 mm dough tube, a Ø30x370 mm screw mixer shaft, and a gear system for heavy loads. Third, a packaging machine equipped with a 1500x800x700 mm table stand. This program has succeeded in increasing partners' production capacity, improving the hygiene of the production process, and reducing dependence on manual labor. In addition, this activity also provides appropriate technology transfer to local communities and strengthens the regional economy by increasing the productivity of fishery product processing business groups.